2018
DOI: 10.21608/jpp.2018.36338
|View full text |Cite
|
Sign up to set email alerts
|

Response of some Yellow Maize Hybrids (Zea mays L.) to Sowing Date under Toshka Conditions

Abstract: In order to study the effect of sowing date on performance of hybrids yellow maize, tow field experiment were conducted in two successive summer seasons 2016 and 2017 at the Toshka Experimental station of Desert Research Center, Abu Simbel City, Aswan Governorate. Five sowing dates ( March 1 st , March 20 th , April 10 th , July 20 th and August 10 th ) under studied on the yield and its attributes of four yellow maize hybrids(S.C. 168, S.C. 176,T.W.C.353 and T.W.C. 360 ). Results indicated that sowing date an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
4
6
0
Order By: Relevance
“…El-Mekser et al (2020) and Abd-Elaziz et al (2020) they revealed that the three way cross 353 was the earliest hybrid for number of days to 50% tasseling (58.3 days) and (62.62 days), respectively. These results are in line with those reported by Zaki et al (2016), Hassaan (2018), andEl-Hosary et al (2019) and Yasser et al (2020).…”
Section: Results and Discussion I-earliness And Vegetative Characteristics: Hybrid Differences (M)supporting
confidence: 93%
See 2 more Smart Citations
“…El-Mekser et al (2020) and Abd-Elaziz et al (2020) they revealed that the three way cross 353 was the earliest hybrid for number of days to 50% tasseling (58.3 days) and (62.62 days), respectively. These results are in line with those reported by Zaki et al (2016), Hassaan (2018), andEl-Hosary et al (2019) and Yasser et al (2020).…”
Section: Results and Discussion I-earliness And Vegetative Characteristics: Hybrid Differences (M)supporting
confidence: 93%
“…Yasser et al (2020) explained that S.C.168 hybrid had the highest grain yield and its components followed by SC 176, then TWC 321 maize hybrid. These results are in harmony with those reported by Zaki et al (2016), Gomaa et al(2017), Hassaan (2018) Concerning the influences of the foliar application by amino cat fertilizer on yield and yield components, data in Tables 4 and 5 indicated that foliar application of AA significantly increased plant height (212.7 and 212.8 cm), ear length (17.74 and 17.67 cm), number of ears plant -1 (1.09 and 1.10 ear) and grain yield of maize (3.02 and 3.06 ton fed -1 ) by increasing AA concentrations up to 200 cm 3 fed -1 in the 2018 and 2019 seasons, respectively. The superiority of 200 cm 3 fed -1 over 100 cm 3 fed -1 from amino cat fertilizer on maize plants might be attributed to its greatest positive effect on growth traits (Table 4), and more dry matter accumulation and stimulated the building of metabolic products that translocated to grains.…”
Section: Ii-yield and Its Attributes: Hybrid Differences (M)supporting
confidence: 93%
See 1 more Smart Citation
“…These outcomes might be recognized to the variations in their genetical makeup. Hassaan (2018), El-Mekser et al (2020 and Ul-Allah et al (2020) approved these findings.…”
Section: Maize Hybrids Performancementioning
confidence: 90%
“…Significant varietal differences in growth, yield components, yield and grains quality of maize were observed by Mahgoub and El-Shenawy (2006), Khalil (2007), El-Sharifi et al (2009), Abdou et al (2012), Attia and El-Dissoky (2016), Awadalla and Morsy (2016) and Ul-Allah et al (2020). Hassaan (2018) indicated that maize hybrids (SC 168,SC 176,TWC 353 and TWC 360) considerably affected plant height, number of grains per row, 1000-kernal weight and yield of grain in kg fed -1 . Manjunatha et al (2018) discovered that significant variations among maize hybrids were observed in yield and yield component.…”
Section: Introductionmentioning
confidence: 99%